Integration of a battery of biomarkers to evaluate the health status of field-collected frogs of Leptodactylus luctator living in ecosystems with different anthropogenic disturbances - Bahl, María Florencia (2024)
Amphibians are the most threatened group of vertebrates because they have certain biological and ecological characteristics that make them sensitive to environmental changes. The aim of this study was to evaluate the health status of field-collected adult frogs of Leptodactylus luctator (Amphibia, Anura) living in sites with different anthropogenic disturbances (florihorticulture, petrochemical industry and sewage discharges) and a reference site without any detectable influence of such activities. To this end, a battery of 21 biomarkers (hematological, biochemical and individual biomarkers) was studied using a multivariate approach that allows us to evaluate the relationship between them and provide information on their usefulness. The frogs at the florihorticulture, petrochemical and sewage discharges sites exhibited several biomarkers far from homeostasis. In addition, we identified 11 of 21 biomarkers that were useful indicators of the health status of the frogs and allowed discrimination between study sites in the following order: lymphocytes (98 %), neutrophils (45 %), hemoglobin (42 %), monocytes (41 %), fat body index (35 %), eosinophils (35 %), hepatosomatic index (33 %), mean corpuscular hemoglobin (32 %), thrombocytes (27 %), catalase in liver (26 %), and GST in liver (26 %). The results suggest that hematological biomarkers contribute the most to site separation, whereas biochemical biomarkers contribute the least. The integral interpretation of the results also allowed us to diagnose the different health status of L. luctator: The frogs from the petrochemical industry were the most negatively affected, followed by the frogs from the sewages discharges and finally the frogs from the florihorticulture and reference sites. This is the first field study with anurans in which so many biomarkers were examined.